Patterns of repeated diagnostic testing for COVID‐19 in relation to patient characteristics and outcomes. (19th December 2020) - Salerno, S.; Zhao, Z.; Prabhu Sankar, S.; Salvatore, M.; Gu, T.; Fritsche, L. G.; Lee, S.; Lisabeth, L. D.; Valley, T. S.; Mukherjee, B.
Abstract: Background: Whilst the COVID‐19 diagnostic test has a high false‐negative rate, not everyone initially negative is re‐tested. Michigan Medicine, a primary regional centre, provided an ideal setting for studying testing patterns during the first wave of the pandemic. Objectives: To identify the characteristics of patients who underwent repeated testing for COVID‐19 and determine if repeated testing was associated with downstream outcomes amongst positive cases. Methods: Characteristics, test results, and health outcomes for patients presenting for a COVID‐19 diagnostic test were collected. We examined whether patient characteristics differed with repeated testing and estimated a false‐negative rate for the test. We then studied repeated testing patterns in patients with severe COVID‐19‐related outcomes. Results: Patient age, sex, body mass index, neighbourhood poverty levels, pre‐existing type 2 diabetes, circulatory, kidney, and liver diseases, and cough, fever/chills, and pain symptoms 14 days prior to a first test were associated with repeated testing. Amongst patients with a positive result, age (OR: 1.17; 95% CI: (1.05, 1.34)) and pre‐existing kidney diseases (OR: 2.26; 95% CI: (1.41, 3.68)) remained significant. Hospitalization (OR: 7.88; 95% CI: (5.15, 12.26)) and ICU‐level care (OR: 6.93; 95% CI: (4.44, 10.92)) were associated with repeated testing. The estimated false‐negative rate was 23.8% (95% CI: (19.5%, 28.5%)). Conclusions: Whilst most patients were tested once and received a negative result, a meaningful subset underwent multiple rounds of testing. These results shed light on testing patterns and have important implications for understanding the variation of repeated testing results within and between patients. Abstract :